E-106 Technical nuances and outcomes of telescoping pipeline flow-diverters: a multicenter study. (23rd July 2022) - Baker, C; Hunsaker, J; Folzenlogen, Z; Case, D; Pride, G; White, J; Roark, C; Welch, B; White, A; Seinfeld, J; Grandhi, R; Taussky, P
Abstract : Purpose: The use of multiple overlapping devices has increased the utility of flow-diverters (FD) by allowing for more impermeable coverage, as well as provide the ability to off-set landing zone sites and extend treatment constructs. This technique has unique challenges and risks compared to single device deployment that has not been well described in literature. Methods: Data from three neurovascular centers were retrospectively queried to identify patients with intracranial aneurysms that were treated with telescoping pipelines. Patient and aneurysm characteristics, as well as outcomes including Raymond-Roy occlusion classification, Modified Rankin Scale, and complications were gathered. The authors then used case examples to illustrate various technical nuances and indications for telescoping. Results: In total, 46 patients had 48 intracranial aneurysms treated. Twelve patients (26%) presented with subarachnoid hemorrhage. The most common aneurysm morphology was saccular (21 patients, 44%), followed by fusiform (11 patients, 23%), pseudoaneurysm (9 patients, 19%) and blister (7 patients, 15%). Distribution of telescoping type was as follows: 21 aneurysms (44%) were treated with proximal extension, 13 aneurysms (27%) with distal extension and 14 aneurysms (29%) with FD placement inside one another. Thirty patients (70%) had complete aneurysm occlusion at follow-up. Two patients (4%) had to be retreated. Four patients (9%) had a permanent intraprocedural complication. Conclusion: We present a multi-institutional case series that focuses on the technical nuances and challenges of telescoping pipelines for the treatment of intracranial aneurysms. These data indicate a higher-than-expected complication rate that is likely due to the technical complexity of these cases. We hope these cases further educates the reader on the indications and challenging aspects of telescoping pipeline devices. Disclosures: C. Baker: None. J. Hunsaker: None. Z. Folzenlogen: None. D. Case: None. G. Pride: None. J. White: None. C. Roark: None. B. Welch: None. A. White: None. J. Seinfeld: None. R. Grandhi: None. P. Taussky: None.